Retrospective Analysis of Full-Arch Zirconia Rehabilitations on Dental Implants: Clinical Outcomes and Patient Satisfaction - Vincenzo Marchio; Chiara Cinquini; Fortunato Alfonsi; Stefano Romeggio; Marco Stoppaccioli; Francesco Zingari; Mattia Priami; Antonio Barone (Applied Sciences)
The use of zirconia for full-arch Implant-Supported Fixed Complete Dental Prostheses (ISFCDPs) is common and reliable, with different techniques available for their design and fabrication. This retrospective study investigated prosthetic and implant survival/success rates and patients’ satisfaction for ISFCDPs produced with three different techniques: zirconia-on-titanium (milled zirconia arch glued to a titanium bar), progressive monolithic zirconia (entirely made of zirconia and directly screwed to the implants) and zirconia-on-zirconia (milled esthetic zirconia crowns glued to a milled high resistance zirconia frame). Fourteen patients (five males, nine females) aged 52–80 and treated with 14 ISFCDPs (86 implants) were included in this analysis. The mean follow-up at the time of recall was 36 months. Prosthetic and implant-related success rates were, respectively, 92.86% and 95.35%. No failures have been reported. One case of prosthetic chipping was observed; however, it was successfully repaired intraorally. Patients’ satisfaction was high: 78.57% were completely satisfied, 14.53% very satisfied and 7.14% satisfied. In conclusion, all the patients recommend treatment with ISFCDPs as full-arch prosthetic rehabilitation. The present study demonstrates positive clinical outcomes and high patients’ satisfaction. Further long-term, prospective studies with a larger cohort of patients are needed to confirm the advantages of the different prosthetic designs.